Comment on Schubert et al. 2020. Muknalia minima from the Yucatán of Mexico is synonymous with the collared peccary, Pecari tajacu (Artiodactyla: Tayassuidae). Open Quaternary, 6: 8, pp. 1–9. DOI: https://doi.org/10.5334/oq.84. (22nd June 2021) - Stinnesbeck, Sarah R.; Stinnesbeck, Wolfgang; Frey, Eberhard; Olguín, Jerónimo Avilés; González, Arturo H. González
Schubert and colleagues have recently criticized our assessment of the mandibular ramus of a small peccary from Muknal cave in Quintana Roo, Mexico, to a new genus and species, Muknalia minima Stinnesbeck et al. 2017 . They considered this assignation as invalid and the unique morphologies of the taxon to be the result of breakage and human modification. We strongly disagree with this interpretation and maintain our original view of a new genus and species.